Uric acid/superoxide dismutase can predict progression of gestational hypertension to preeclampsia - Yun, Lin; Yu, Xiaoqian; Xu, Rui (Frontiers in Cardiovascular Medicine, 2023)
Introduction Preeclampsia (PE), at early onset, is likely to be diagnosed as gestational hypertension (GH). Some cases of GH rapidly progress to PE within a short period of time, increasing the mortality rate of pregnant women and adverse events in neonates during the peripartum period. Oxidative stress participates in the occurrence and progression of PE. However, it is unknown whether the progression of GH to PE can be predicted. Methods A total of 1548 patients diagnosed with PE (649 cases) or GH (899 cases) from January 2016 to June 2022 were selected as the study subjects. The 1548 patients were randomly divided into the training set (1083 cases) and the validation set (465 cases) in a 7:3 ratio. General and clinical data were collected to construct a risk factor prediction model for PE. Results We found that (1) Systolic blood pressure (SBP), and uric acid (UA)/ superoxide dismutase (SOD) were the risk factors for the progression of GH to PE; (2) A nomogram was constructed from the prediction model, and the area under the curve (AUC) was 0.95, with a sensitivity of 87.4%, a specificity of 92.8%; (3) Build a model simplified scoring system. PE was most strongly predicted by UA/SOD (100 points), SBP (29 points), and serum potassium (19 points). The AUC was 0.92, with a sensitivity of 91.0%, a specificity of 81.7%. The clinical decision analysis curve shows that the model exhibits positive benefits when the threshold probability is at 0.01–0.91. Conclusion These findings show that UA/SOD can predict progression of GH to PE.